Chronic sacroiliac joint pain treated with pulsed radiofrequency ablation - Farid Yudoyono; Dewi Pratiwi; Hendra Gunawan; Deasy Herminawaty (Neurologico Spinale Medico Chirurgico, 2020)
Chronic sacroiliac joint (SI) pain can cause disability in an aging society. Effective treatment of low back pain (LBP) originating from sacroiliac joints is difficult to achieve. We report the successful treatment of pulsed radiofrequency (PRF) ablation in a patient with chronic SI joint pain. There were no post-interventional complications. Clinical improvement reported after 12 months.